Identifikasi Tumbuhan Penghasil Polen dari Madu Lebah Tanpa Sengat di Belitung: Identification of Plants as Pollen Source in Honey of Stingless Bee Heterotrigona itama and Tetragonula laeviceps from Belitung - Setya Priambudi , Abyan; Raffiudin, Rika; Ratna Djuita, Nina (Departemen Biologi, Institut Pertanian Bogor, 2021)
Stingless bees forage to the flower for nectar and at the same time, pollen also trapped in the body hairs of the bees. Mostly pollen was concentrated into the pollen basket and transferred to the pollen and honey pot in the stingless bee nest. Pollen is male gametophytes of seed plants which have various of shapes, sizes, and ornamentations. This palynology study was aimed to identify the plants of pollen source that were found in honey of stingless bee Heterotrigona itama and Tetragonula laeviceps in Belitung and to analyze characteristics of the pollen. Pollen was extracted from honey and conducted the acetolysis and identification of the pollen in honey. We found 11 and 19 plant species as pollen soirce in the honey of H. itama and T. laeviceps, respectively. Pollen from Macaranga tanarius (23.72%) and Cocos nucifera (22.53%) were the two most dominant species on the H. itama honey. Pollen from Ageratum conyzoides (16.36%) are most often found in T. laeviceps honey. The most common pollen in honey of H. itama and T. laeviceps were from Arecaceae with a total of three species. Pollen from plants with tree habitus is most commonly found in honey of both species of stingless bees.